Risk factors for the rupture of intracranial aneurysms: a systematic review and meta-analysis - Ma, Jinyuan; Zheng, Yuehua; Li, Puxian; Zhou, Tao; Sun, Zhen; Ju, Tongze; Li, Aijun (Frontiers in Neurology, 2023)
Purpose: To identify potential risk factors for aneurysm rupture by performing a systematic review and meta-analysis. Materials and Methods: We systematically searched the PubMed, Embase, and Cochrane Library electronic databases for eligible studies from their inception until June 2023. Results: Eighteen studies involving 17,069 patients with unruptured intracranial aneurysm (UIA) and 2,699 aneurysm ruptures were selected for the meta-analysis. Hyperlipidemia (odds ratio [OR]: 0.47; 95% confidence interval [CI]: 0.39-0.56; p<0.001) and a family history of subarachnoid hemorrhage (SAH) (OR: 0.81; 95% CI: 0.71-0.91; p=0.001) were associated with a reduced risk of aneurysm rupture. In contrast, a large-size aneurysm (OR: 4.49; 95% CI: 2.46-8.17; p<0.001), ACA (OR: 3.34; 95% CI: 1.94-5.76; p<0.001), MCA (OR: 2.16; 95% CI: 1.73-2.69; p<0.001), and VABA (OR: 2.20; 95% CI: 1.24-3.91; p=0.007) were associated with an increased risk of aneurysm rupture. Furthermore, the risk of aneurysm rupture was not affected by age, sex, current smoking), hypertension, diabetes mellitus, a history of SAH, and multiple aneurysms. Conclusions: This study identified the predictors of aneurysm rupture in patients with UIAs, including hyperlipidemia, a family history of SAH, a large-size aneurysm, ACA, MCA, and VABA; patients at high risk for aneurysm rupture should be carefully monitored.